The making of the maker : a practice-based exploration into the process of signification as a mutually constitutive process for artist and artwork - Ferreira, Doret Jr (Johanna Dorothea) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.